2023
DOI: 10.20937/atm.53103
|View full text |Cite
|
Sign up to set email alerts
|

Application of geostatistical models for aridity scenarios in northern Mexico

Abstract: An annual mean temperature map was calculated using the Kriging interpolation method for the north-central zone of Mexico to obtain the current aridity, as well as, possible scenarios for the near and distant future. The altitudinal gradient was estimated by linear regression and it was used to estimate the mean temperature. Climate Influence Areas (CIA) were obtained by superimposing the official precipitation layer and the annual mean temperature la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…Nonetheless, the weighed components resulting from the AHP exhibited results for the water poverty of these municipalities that agree with the estimations argued by other studies and experts [8,24,25,36,48,52,65]. The WPIs calculated on the basis of AHP multicriteria decision making indicated that Dr. Arroyo and Aramberri were the most vulnerable municipalities in terms of water poverty.…”
Section: Wpi Performancesupporting
confidence: 85%
See 3 more Smart Citations
“…Nonetheless, the weighed components resulting from the AHP exhibited results for the water poverty of these municipalities that agree with the estimations argued by other studies and experts [8,24,25,36,48,52,65]. The WPIs calculated on the basis of AHP multicriteria decision making indicated that Dr. Arroyo and Aramberri were the most vulnerable municipalities in terms of water poverty.…”
Section: Wpi Performancesupporting
confidence: 85%
“…We propose the WPI as a versatile and replicable model for evaluating the causes and impacts of water scarcity and its relation to poverty and socioeconomic conditions. By employing the WPI, studies have evaluated water scarcity and vulnerability at different scales and seasons, national or regional [6,23,31,[44][45][46][47][48]. Despite these evaluations demonstrating the significance of socioeconomic conditions in water scarcity, comparability is hindered by variations in methodology and scale.…”
Section: Of 20mentioning
confidence: 99%
See 2 more Smart Citations
“…However, limitations in aridity measurements have been prevalent in developing countries due to the lack of measured PET data and challenges with accurate PET estimations (Sahin, 2012). A more comprehensive evaluation of aridity aims to overcome these limitations through the application of geostatistical interpolation models (De Jesus Correa‐Islas et al, 2023). This study predicted future aridity scenarios in northern Mexico that may worsen the current situation, potentially leading to a gradual decline in humidity and environmental resilience.…”
Section: Resultsmentioning
confidence: 99%